Development of Real-Time Water Level Monitoring System for Flood Mitigation and Prediction Using Wireless Network Sensors - Nur Ainina Asyra, A. Kadir; Ahmed, Ehab Ali; Syafiq Fauzi, Kamarulzaman (2016)
Real Time Water Level Monitoring System with Wireless Network Sensors for Flood was developed to help the population on flood prone areas especially for those who live nearby by the riverbank to make early preparation before the flooding. In the system, sensors and software will be developed for measuring the fluctuation of water level. The measurement will be collected for a period to measure the water level according to nodes, and the data will be analyzed to visualizes the fluctuation according to the nodes alongside the riverbank. The system will be receiving the data from the sensors through Global System for Mobile communication (GSM). Data collected will automatically be stored into the database. The data will be used to analyze the pattern of water level fluctuation. This analysis may be helpful in prediction of future flooding.